How does the innovative factor allocation promote the high quality development of manufacturing industry? - Cui Li; Jie Zhu; Changqi Tao (Journal of Innovation & Knowledge (JIK), 2024)
Digital technology changes the innovation mode, and the innovative factors among innovation subjects will be digitally empowered. The government plays a very important role in determining the allocation of innovative factors. Therefore, it is necessary to clarify the main source of power for the high-quality development of the manufacturing industry in the future, so as to help the government to use digital technology to adjust the innovative factors allocation appropriately. We used systematic dynamic model to portray the innovation mechanism of manufacturing industry and set relevant parameters based on previous literature to predict the variation of innovation under different scenarios. It was found that government expenditure on science and technology can significantly improve innovation performance, followed by information expenditure, while government expenditure on education needs to reach a certain scale before it can play a positive role. However, after passing a certain threshold, education has a significantly positive role in promoting innovation.Therefore, when the government adjusts the structure of expenditures, it should ensure long-term and stable education expenditure, give full play to the role of innovative factors such as talents. It should also ensure the construction and maintenance of information infrastructure, so as to enhance the industry-university-research collaborative innovation in the digital era and promote high-quality development of manufacturing industry.
Keywords: A10; C53; E17; H50; 650; Digital empowerment; Innovative factors; System dynamic model; Manufacturing industry